Keterampilan Pengelolaan Kelas Mahasiswa PGSD Pada Praktik Mengajar di Sekolah Dasar - Maharani Putri Kumalasani; Dian Ika Kusumaningtyas; Varicha Nur Maulidia (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
Class management skills are one of the primary teaching skills that are important to be mastered by prospective teacher students. Therefore, before students enter the field, they must ensure their ability to manage the class. The learning process will be conducive if the teacher manages the class well enough to support the learning process. The purpose of this study was to take a deeper look at the ability to manage student-teacher classes. This study uses a qualitative research method with a descriptive approach. With the research stages (1) Preparation Stage, in the preparation stage, the researcher prepares a research plan and makes interview, observation, and documentation guidelines. (2) Implementation phase, researchers conduct field studies by carrying out observations and interviews, as well as taking documentation with (3) Findings Researchers analyze findings and draw conclusions from research results and continue with the last stage, namely (4) Research Reporting Stage using the method in collecting data by observation, interviews, and documentation. This study's results indicate that prospective teacher students' ability to manage the class is excellent. Each indicator in managing the class is carried out according to the student's experience demonstrating basic teaching skills. Researchers hope for future researchers to look more deeply into prospective teacher students' ability to master other basic teaching skills in more detail and innovatively.